Self-Service Optimization: Comprehending Customer Satisfaction - Suryawijaya, Tito Wira Eka; Utomo, Muhammad Tata Rizky Setyo; Rahayuningtyas, Tri Esti (Jurnal Manajemen (Edisi Elektronik), 2023)
Today, washing clothes is a separate problem for some people. This is because not a few people have very busy activities in their daily lives. Indirectly, they decided to use a laundry service which was considered fast and efficient due to the limited time they had. Self-service laundry service is a laundry service that has a customer service system that will wash their own clothes at the laundry in a short time. Self-service based methods have developed very rapidly in various business sectors. This study purpose is to determine the level of customer satisfaction and their level of loyalty to self-service-based laundry services. This study uses the SEM-PLS analysis method. Data is obtained through observation with business owners/supervisors in order to understand the patterns and mechanisms of implemented marketing communications. As well as distributing an online questionnaire based on The Flower of Service which was filled in by 302 respondents to understand the level of customer satisfaction. This study reveals that self-service-based laundry services are supported by optimizing business strategies, especially in digital-based integrated service marketing communications that have been carried out. The results of the study revealed that customers stated quite high levels of satisfaction and loyalty. This research contributes to the service marketing literature by revealing the perspectives of customer satisfaction and loyalty in self-service-based service businesses. There have been many studies conducted to discuss this laundry service business. However, there are no research findings regarding Self-service Optimization.